Recollections of daughters of mothers with a psychotic disorder : an exploration of the recollections of adult daughters on being raised by a mother with a psychotic disorder - Day, Sarah (My University, 2015)
This study analysed the retrospective recollections of adult daughters on being raised by a mother with a severe mental illness. Much research (Apfel & Handel, 1993; Beardslee et al., 1998; Hall, 2004; Rutter, 1989, 1990; Smith, 2004) has focused on the genetic transmission of risk and little research has been done on the subjective experiences of these children (Gladstone, Boydell & McKeever, 2006; Mordoch & Hall, 2002). This research utilised interpretive phenomenological analysis (IPA) to examine the retrospective accounts, generated by semi-structured interviews, of five adult daughters of a mother with a severe mental illness. These accounts produced six main themes and several sub-themes. The participants reflected that their mothers’ severe mental illness had a profound effect on their development and on their relationships with their mothers. Many of the participants report that they were required to mature prematurely and had to take on inappropriate levels of responsibility, such as taking care of younger siblings, household duties and, in one case, being a caregiver for her mother. Feelings of anger and guilt were commonplace among the recollections. The participants’ recollections included instances of physical and/or emotional abuse and neglect. Many of the participants report that these experiences led to a low selfesteem that has persisted into their adult life. Some of the participants reported current and past difficulties with intimate relationships which they attribute directly to their experiences of living with their mentally ill mother. Each of the participants reported that protective relationships were important coping mechanisms. Four of the participants entered therapy and found that this provided help in understanding their current actions and feelings. The diagnosis provided a ‘scapegoat’ for many of the participants and allowed them to attribute their mother’s behaviour to her illness.
Research Report School of Human and Community Development University of the Witwatersrand 16 February 2015